Meta-Analisis Mengenai Pembelajaran Berdiferensiasi yang Meningkatkan Hasil Belajar Siswa - Angga Dinata (PT PUSTAKA CENDEKIA GROUP, 2024)
Differentiated instruction is a pedagogical approach that tailors teaching methods to the diverse needs, interests, and abilities of students. This study aims to analyze the impact of differentiated instruction on student learning outcomes by reviewing 10 journals published in the last five years. The method used is quantitative analysis, involving the collection of data on student learning outcomes before and after the implementation of differentiated instruction. The analysis results indicate that differentiated instruction consistently improves learning outcomes, with an average increase ranging from 15% to 25%. These findings suggest that tailored teaching strategies can enhance student engagement and academic achievement. This study recommends the implementation of differentiated instruction in teaching practices and emphasizes the need for training for educators to effectively apply this approach.